2021
DOI: 10.1155/2021/6656176
|View full text |Cite
|
Sign up to set email alerts
|

Economic Policy Uncertainty Linkages among Asian Countries: Evidence from Threshold Cointegration Approach

Abstract: This paper employs the threshold cointegration methodology to assess the long- and short-run dynamics of asymmetric adjustment between economic policy uncertainty (EPU) of China-India, China-Japan, China-Korea, India-Japan, India-Korea, and Japan-Korea pairs using monthly EPU data ranging from January 1997 to April 2020. The relationship between the EPU pairs is examined in terms of Engle-Granger and threshold cointegrations. The findings provide evidence of long-run threshold cointegration and that the adjust… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 76 publications
1
4
0
Order By: Relevance
“…However, GEPU lags for India, but has a potential to lead or lag for Russia and China in the medium-term. This outcome contributes to the findings of Osei et al [ 106 ] that EPU from China responds quickly to a rise in value of other ASIAN countries’ EPU indices, which may require possible policy uncertainty synergies and spillovers among the Asian economies. Despite the result of this study, Carré and L’œillet [ 107 ] in their review indicated that the nexus between finance-growth nexus is inconclusive.…”
Section: Conclusion and Policy Implicationsupporting
confidence: 76%
“…However, GEPU lags for India, but has a potential to lead or lag for Russia and China in the medium-term. This outcome contributes to the findings of Osei et al [ 106 ] that EPU from China responds quickly to a rise in value of other ASIAN countries’ EPU indices, which may require possible policy uncertainty synergies and spillovers among the Asian economies. Despite the result of this study, Carré and L’œillet [ 107 ] in their review indicated that the nexus between finance-growth nexus is inconclusive.…”
Section: Conclusion and Policy Implicationsupporting
confidence: 76%
“…e adverse long-term influence of GEPU on stock markets is not far from the results obtained by prior empirical studies [46,91]. It is not startling to find that GEPU adversely impact on stock returns of China and India because Osei et al [92] made it clear that EPU from China and India respond quickly to a rise in value of other ASIAN countries' EPU indices, which may require possible policy uncertainty synergies and spillovers among the Asian countries. We advocate that stock markets of BRICS economies are vulnerable to external shocks and uncertainty in the long-term perspective which is contrary to the findings of Hung et al [51,93].…”
Section: Discussionmentioning
confidence: 87%
“…An attempt has been made in several studies to capture the relevance of EPU across domestic and global economies (Bai et al 2019;Akadiri et al 2020;Abakah et al 2021;Osei et al 2021;Yang et al 2021;Zhou et al 2022). For instance, in the recent study by Zhou et al (2022), the spillover effects, the dynamic characteristics of the EPU spillover network, and the corresponding impact of the coronavirus (COVID-19) pandemic on these spillover effects across 19 countries were investigated.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Moreover, without evidence of a significant impact on net spillovers, COVID-19 deaths and new infection cases exert a statistically significant effect on transmission and reception directional EPU spillovers. Like Zhou et al (2022), with the complex network analysis, the effects of EPU have been linked to market systems across global economies, including the Asia-Pacific region (Osei et al 2021;Yang et al 2021), and the selected developed economies (Abakah et al 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation